Aminopropyl group-modified SBA-15 covalent attachment Mn(salen) complexes as catalysts for styrene epoxidation. (2nd January 2016) - Liu, Lili; Hu, Jianglei; He, Jiaojiao; Lu, Haojie; Xu, Yong; Shi, Fengwei
GRAPHICAL ABSTRACT: Abstract: A series of aminopropyl group-modified ordered mesoporous silica materials impregnated with Mn(salen) were prepared using successive grafting procedures. The prepared composite catalysts were well characterized by inductively coupled plasma atomic emission spectroscopy, Fourier transform-infrared, UV–Vis diffuse reflectance spectroscopy, X-ray diffraction analysis, and transmission electron microscopy in order to confirm the structure integrities of the Mn(salen) units after the incorporation, to evidence the formation of a covalent bond between the starting Mn(salen) units and the aminopropyl group-modified SBA-15 matrix in the presence of NaOH by abstraction of an HCl molecule. These heterogeneous catalysts exhibited comparable catalytic activity and selectivity to those of the homogeneous counterpart in the epoxidation of styrene by using NaClO as oxidant. In addition, the effects of key reaction parameters, including the loadings of the neat Mn(salen), molar ratios of NaClO to styrene, and PPNO amount on the reactivity and selectivity, were also studied. Finally, the reusability of the prepared heterogeneous catalyst was evaluated.